Sustainability of Dr. Meilė Lukšienė’s Teaching in the Context of the National Education Strategy - Ališauskas, Ričardas; Dukynaitė, Rita (Pedagogika, 2015)
The article provides the analysis of scientific creations by Dr. Hab. Meilė Lukšienė in the context of the National Education Strategy 2013–2022. It aims at evaluating the potential of persistence and sustainability of M. Lukšienė’s scientific thought and revealing the fact that works by M. Lukšienė still bear relevance to implementation of the recent National Education Strategy. Moreover, an original interpretation of the National Education Strategy in the context of the State Progress Strategy “Lithuania 2030” is provided and the most relevant goals set in the National Education Strategy for the school system are presented in the article. The aim of this article is to disclose the relation between contributions by Meilė Lukšienė and the National Education Strategy 2013–2022 as well as to demonstrate the potential for employing M. Lukšienė’s works in further reforms of education in Lithuania. The methods applied in the study: analysis of research and documentary sources, synthesis of a range of scientific and strategic vision ideas, and shaping of strategic policy for further reconstruction of Lithuania’s education.